2021
DOI: 10.1155/2021/7190152
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of Bacteriocin-Like Inhibitory Substances Produced by Streptomyces sp. Isolated from the Gut of Chanos chanos

Abstract: Bacteriocin-like inhibitory substances (BLIS) have sparked great interest because of their promising use in food as natural antimicrobial agents. In this work, six Streptomyces isolates obtained from the gut of Chanos chanos demonstrated their ability to produce extracellular metabolites with inhibitory activity against Salmonella enterica serovar Typhimurium, Escherichia coli, Listeria monocytogenes, and Staphylococcus aureus. Exposure of the extracellular metabolites to proteolytic enzymes (i.e., proteinase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
3
12
0
1
Order By: Relevance
“…However, the slight increase of the load 2 h after the introduction of the bacteriocin is due to the decrease of the bacteriocin concentration in the medium; this decrease can be linked to the action of the proteolytic enzymes synthesized by the strain or bacteriocin titration. Similar results have been obtained by [43][44][45].…”
Section: Mode Of Action Of C4bsupporting
confidence: 89%
“…However, the slight increase of the load 2 h after the introduction of the bacteriocin is due to the decrease of the bacteriocin concentration in the medium; this decrease can be linked to the action of the proteolytic enzymes synthesized by the strain or bacteriocin titration. Similar results have been obtained by [43][44][45].…”
Section: Mode Of Action Of C4bsupporting
confidence: 89%
“…Antibacterial activity and protein analysis showed that BLIS with MW <3 and 3-10 kDa were the most potent fractions because they had the highest BLIS-specific activity. Potential fractions also showed their sensitivity to proteolytic enzymes (proteinase-K, trypsin, and pepsin) [ 18 ]. The fraction was further fractionated by gel filtration chromatography to obtain semi-purified BLIS.…”
Section: Resultsmentioning
confidence: 99%
“…BLIS produced by six Streptomyces isolated from the gut of Chanos chanos: S. variabilis SCA5 (S5), S. variabilis SCA11 (S11), S. variabilis AIA10 (A10), S. labedae SCA8 (S8), S. globisporus AIA12 (A12) and S. misionensis AIA17 (A17) [15][16][17] with the method and culture conditions according to Kurnianto et al [18]. BLIS in freeze-dried form dissolved in distilled water.…”
Section: Fractionation Blis By Gel Filtration Chromatographymentioning
confidence: 99%
“…This solvent is described as the ideal solvent for obtaining metabolites with antibacterial activity. This may be because it is possible that actinobacteria, especially streptomyces, produce semipolar antibacterial compounds so that they can be extracted by solvents with the same polarity as ethyl acetate, as mentioned in the study by Kurnianto et al [ 180 ]. Likewise, Satish et al evaluated the activity of extracts obtained from different solvents such as chloroform, butanol, and ethyl acetate against MRSA, finding that only the extracts obtained with the latter exhibited antibacterial activity [ 87 ].…”
Section: Discussionmentioning
confidence: 99%